2017
DOI: 10.3923/pjbs.2017.423.435
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological Changes of Biodiesel Producer Plants Reutealis trisperma (Blanco) in Response to Gold-Mining Wastewater

Abstract: Gold mine wastewater treatment caused all the plants to undergo stress characterized by the increase of malondialdehyde and the decrease of chlorophyll content and leaf growth of R. trisperma, even though there was variation among the varieties. KM2 and KD2 had the best performance among all varieties in response to gold-mine wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Ricinus communis (castor bean) has also been known to have the ability to stabilize residues and lower metal levels (Olivares et al 2013), as well as to grow well in the presence of lead (Zhang et al 2015). Reutealis trisperma (candlenut), a tree species, has good adaptability to grow in marginal lands such as posttin mining soil, very dry land, and acidic soils (Pranowo et al 2015), and was able to adapt to the gold mine's liquid waste (Hamim et al 2017). Melia azedarach (melia) was effective to eliminate arsenic contamination (Sarwar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ricinus communis (castor bean) has also been known to have the ability to stabilize residues and lower metal levels (Olivares et al 2013), as well as to grow well in the presence of lead (Zhang et al 2015). Reutealis trisperma (candlenut), a tree species, has good adaptability to grow in marginal lands such as posttin mining soil, very dry land, and acidic soils (Pranowo et al 2015), and was able to adapt to the gold mine's liquid waste (Hamim et al 2017). Melia azedarach (melia) was effective to eliminate arsenic contamination (Sarwar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gold mining managed by both industry and small-scale public mining caused serious environmental damage by producing contaminants in the form of cyanide compounds (Akcil 2003;Hamim et al 2017) and heavy metals such as Pb (Setyaningsih et al 2012) and Hg (Hidayati et al 2009). Heavy metals at certain concentrations are very harmful to living things when they enter to the metabolic system.…”
Section: Introductionmentioning
confidence: 99%
“…Gamal and kaliandra are well known for biomass production, and kemiri sunan and nyamplung are promising for oil seed production. Previous studies suggested that nyamplung is adaptive to waterlogged areas [21][22][23], kaliandra is tolerant to acidic soil (PH 4-5) [24,25], and kemiri sunan is adaptive to marginal land [26]. Gamal is also tolerant to acidic soil [27,28] (Table 1).…”
Section: Forestmentioning
confidence: 99%